The Preparation of An Oleoresin from A Black Pepper Steam Distillation Residue) - Moestafa, Achmad (Balai Besar Industri Agro, 1989)
The single stage solvent extraction of pepper oleoresin did not always give satisfactory results. It might be below or over the standard. To solve the problem the pepper was processed using two stages extraction. First the volatile oil was isolated by means of steam distillation and then the solvent extraction was conducted. To meet the standard qualification the volatile oil and resin were blended. It was found that the best solvent for oleoresin extraction was ethanol. It produced 15% oleoresin and 49% pipperine. The resin and pipperine produced from the distillation residue was more than those from ethylene dichloride extraction.